Caracterização farmacognóstica, físico-química e microbiológica das folhas de anani (Symphonia globulifera Linn. f., Clusiaceae) - SILVA, Eliane Moraes da (Universidade Federal do Pará, 2014)
Symphonia globulifera Linn. f., commonly known as anani cited in reports of popular use in different countries such as Cameroon, and in several regions of Brazil, mainly in the Amazon, in the treatment of skin inflammations, general tonic and laxative for pregnant women, and its latex to be employed against rheumatism and tumors. Although some studies have described the phytochemical profile of S. globulifera, there are no studies to date, assessing the botanical properties, chemical properties (thermal analysis) and pharmaceuticals (spray dryer) of this plant. Thus, classic methodologies were used contained in pharmacopoeias and modern analytical methods. The results for the botanical characterization are: the epidermal cells of both sides of the sheet are heterodimensionais. The stomatal complex is anomocytic type found only on the abaxial surface. The petiole is presented coated plano-convex cells cutinização square and thick. The characterization of the powder are: particle size analysis classifies it as being rude. Loss on drying was 9% in total ash content was 4.3%, with the thermal analysis we observed in TG between 31 and 100°C at the first mass loss of 7.8% in the DTA 64°C and a DSC endothermic event at 84°C an endothermic event of 169 J/g, the spectroscopic profile in the region of the IV suggests the presence of phenolic compounds. While the results for the dye and dried extract are: bulk density of 0.97% g/mL, pH 6; percentage of dry weight of 9% in chemical prospecting verified the presence of saponins, reducing sugars and phenols and tannins to extract and some fractions, the thermal analysis TG was found in a mass loss of 6.55% from 28 to 100°C, only one event in DSC exotherm to 169°C, the spectroscopic profile in the region IV showed bands of strong absorption features of alcohols and phenols. In the study using a spray dryer, excipients that showed the best results were 40% aerosil more aerosil and microcrystalline cellulose in the proportion of 35:5. The extract showed antioxidant properties. The vegetable raw material was also tested for their antimicrobial and antifungal activity, providing positive results for some strains tested and shown bactericidal activity for fractions of iv ethyl acetate and hexane. The extract and the hexane fraction showed fungistatic activity, all these results contribute to future studies with this Plant, thereby increasing their value.